Improving service quality through value proposition: A descriptive single case study - Truong, My (My University, 2022)
This research investigates the current value proposition and service quality challenges at the bookstore chain BK in Vietnam. The study result assists the case firm in increasing its value proposition within the scope of its business model. This research aims to examine the present status of the example firm, compare customer value from a management and customer perspectives, and propose ways to improve BK's service quality through the improvement of a value proposition. The literature review addresses relevant topics in business model, customer preference and business environment analyses to provide a solid background and a wide range of tools for analysis. Then, the study presents an integrated theoretical framework on the relationship between customer needs, firm's competitive advantage (through business model), perceived value and service quality is presented. The research employs a descriptive single-case study approach. One semi-structured interview, four focus groups and desk research are used to collect data, which is then analyzed using thematic analysis. To strengthen the reliability and validity of the study, focus groups were conducted in a standardized environment with participants selected from various client categories. The research was conducted in accordance with Vaasa University's ethical practices. The findings of the study demonstrate that the case company has misjudged the complexity and multidimensionality of client values. Inadequate infrastructure, limited data and the psychology of the customers all present obstacles in determining service quality. Customers are not yet participating in the process of value co-creation due to communication barriers, complex procedures and customer-centric activities. The research also indicates that the company's potential resources are misaligned with its business objectives, resulting in inadequate responses to the external business environment. The PESTLE study highlights the difficulty of implementing digitalization in practice and the emergence of indirect competitors in the online and digital book sectors. Regular competitor analysis is necessary for proactive market responses. The study result assists the organization in improving service quality by engaging consumers in the value co-creation process and appropriately reallocating resources. The proposed new value proposition emphasizes the company's core value, target consumers and social impacts. The result gives recommendations for implementing the new value proposition and business model accordingly. It also assesses the relevancy and applicability of the integrated theoretical framework in practice.
Keywords: value creation; business models; services; customership; quality; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development